If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=-6y-1
We move all terms to the left:
6-(-6y-1)=0
We get rid of parentheses
6y+1+6=0
We add all the numbers together, and all the variables
6y+7=0
We move all terms containing y to the left, all other terms to the right
6y=-7
y=-7/6
y=-1+1/6
| -7-8x=41 | | -7x-28x=0 | | 3x–7=26 | | 5x-12=3*(x-2) | | 25.12=1/3(12,56h) | | 7c+20=20 | | 18=9d | | J=9d | | 4x+3=5x+x | | 0.y-8=9 | | x/1.06=100 | | 30=-6+9x | | 0.15x+0.20x=0.16×25 | | -18+a=-16 | | k4.5+87.7=13.8 | | 33+66=a | | -9+n=7 | | x2+x2=85 | | -8.5x+0.36=-6.44 | | –17−5g+8=15−7g | | -136=-x+4(-8x-1) | | -7-k=-25 | | -5(1-5x)+5(-8x-6)=-24x-8x | | 12-8x=6x | | (81x-36)(81x+36)=0 | | (5x-1)(6x+7)=0 | | -120=-8(1+2r) | | 17x+6=90 | | 25a-28=-9(1-12a) | | 1/2x=1/2x+3 | | 25.68=2x-6.32 | | -6(6k+7)=-150 |